System Oceny Zgodności w Unii Europejskiej i organizacje działające w obszarze jakości: Conformity Assessment System in the European Union and organizations operating in the area of quality - Klimek, Michał (Management and Administration Journal, 2021)
The purpose of this publication is to present with the essential aspects of the Conformity Assessment System in the European Union. The publication will contain the most important characteristics of European organizations working in the field of quality. Will attempt to clarify the terms of the notification of accreditation and certification process and closer management systems, for example, a typical certification body in the country namely the Polish Center for Testing and Certification (notification No. 1434).